IMPLEMENTING TELL (TECHNOLOGY ENHANCED LANGUAGE LEARNING) IN IMPROVING INFORMATICS ENGINEERING STUDENTS’ READING SKILL - Swantika , Ika; Addini, Puteri Fajar; Sitompul, Kristin Lourensi; Harissandi, Refin; Anwar, Rossya Diva (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to obtain some purposes of implementing TELL (Technology Enhanced Language Learning) in improving reading skill especially for informatics engineering students. The quantitative research with explanatory method had been applied as research methodology in this study. There were 20 informatics engineering students as the sample. By going through several stages, the result and conclusion were obtained. First, the Pre-Test had been done to know the student’s basic score in reading skill. Then, the implementation of TELL was conducted to improve the student’s reading skill. The G-meet as the media was utilized as the technology used in language learning. Finally, the Post-test was arranged to know the outcome of implementing TELL. Based on the result, it indicated that the positive impact especially in reading skill was obtained by the students who carried out TELL. It was proven that the post-test score of each student was higher than the pre-test one.